Pembaruan Hukum Pidana Melalui Penerapan Prinsip Insignifikansi: Kajian dalam KUHP Baru Indonesia - Arum, Siti Khumairoh Kusuma; Maulidah, Khilmatin (PT. Kaka Media Visi Sistematis, 2025)
This research is motivated by the phenomenon of over criminalisation in the criminal law system, where minor offences with insignificant impacts are often addressed excessively. Conventional criminal law makes the condition trapped in formalism and positivism, which results in rigid application of law and less responsive to the social context, so that the existing criminal law tends to ignore the difference between significant and insignificant impacts of legal acts. This can cause the punishment to be disproportionate and unfair. Therefore, the principle of insignificance emerged as one of the progressive laws, in order to overcome the injustice caused by the rigid application of law through criminal law reform. The research method used in this research is normative juridical which involves progressive theory as proposed by Dr Satjipto Rahardjo, that the criminal law paradigm emphasises the ability to adapt to changing times and the needs of society so that the law does not become a rigid set of rules, but as a tool to achieve justice and welfare for the community. From this research, it is concluded that the renewal of criminal law through the ratification of the new Criminal Code in Law Number 1 Y ear 2023 by recognising the principle of insignificance is an important step towards a more modern and proportional criminal law system. This principle reduces over-criminalisation of minor offences, conserves legalresources, and replaces the retributive approach with substantive justice. The application of the principle of insignificance in the new Criminal Code also leads to restorative justice by reducing the burden on the justice system and shifting the focus to non-punitive resolution. This principle allows for the resolution of minor cases through alternative mechanisms such as mediation or restitution.However, challenges such as the potential for abuse of discretion and conservative public perceptions need to be addressed with clear regulation, training of law enforcement officers, and public education. With consistent application, this principle can create a more efficient, humane, and just criminal justice system.